Elastic conducting polymer composites in thermoelectric modules - Nara Kim (Nature Portfolio, 2020)
Though deformable thermoelectric materials are desirable for integrating thermoelectric devices into wearable electronics, typical thermoelectric materials are too brittle for practical application. Here, the authors report a high-performance elastic composite for stretchable thermoelectric modules.